Measuring of the Shariah Compliance in the Shariah Cooperative from Maqashid al-Shariah Perspectives - Hanafi, Syahrul; Murtadho, Ibnu; Warseto, Andri (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2026)
Sharia cooperatives are currently growing rapidly and are present in society. However, they face several challenges. One issue is that many still doubt the Sharia-compliant of Sharia cooperatives. Many consider sharia cooperatives to be the same as conventional cooperatives. Therefore, sharia cooperatives must demonstrate their compliance with sharia. This study aims to measure the level of sharia-compliant of sharia cooperatives in Mataram City. The research method used is a descriptive quantitative. This study will involve all sharia cooperatives in Mataram City. The sampling technique used is non-probability sampling with census sampling. The results showed that the BMT Iqtishady and the Gumarang Akbar Sharia Cooperative were the most sharia-compliant cooperatives. Second place was taken by the Al-Mujahidin Mosque Sharia Cooperative in Tanjung Karang Permai and the Bumi Gora Mandiri Sharia Cooperative. Third place went to Sepakat Sejahtera Sharia Cooperative. Based on the research results, the majority of the sampled Sharia cooperatives exhibit a high level of Sharia compliance. This study complements prior research on the Sharia compliance of financial institutions by adding a measurement model grounded in maqashid sharia.